Напорное бетонирование монолитных конструкций и сооружений - Чирков Юрий Борисович (БС, 1989)
Экземпляры: КХ (20100929) / Инвентарный номер: 932353 / Цена: 0.50 / Сис.шифр: 38.6 / Авт.знак: Ч-65 / ГРНТИ: 67 / ББК: 38.626.1